Workers go shopping in Argentina the rise of popular consumer culture - Milanesio, Natalia, 1974-; ProQuest (Firm) (Albuquerque : University of New Mexico, 2013)
"Dr. Milanesio examines the ways mass consumption transformed Argentina in the twentieth century in a comprehensive analysis of the relations between consumers, goods, manufacturers, advertisers, and the state during Juan Peron's reign. She examines the social and political changes that occurred when the general population became consumers of industrial goods and participants in consumption"--Provided by publisher.
Industry, wages, and the state: the rise of popular consumer culture -- Surveys and campaigns : discovering and reaching the worker-consumer -- Commercial culture becomes popular : advertising and the challenges of a changing market -- How can a garbage collector be on the same level as we are? : upper- and middle-class anxieties over working-class consumers -- Love in the time of mass consumption -- Tales of consumers : memory and working-class material culture -- Epilogue : consumer culture today.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Consumption (Economics) -- Argentina; Consumers -- Argentina -- History -- 20th century; Working class -- Argentina -- History; Argentina -- Economic conditions -- 20th century; Electronic books